2017
DOI: 10.13189/ujer.2017.050108
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Learning Style, Test Anxiety and Academic Achievement

Abstract: This study aimed to investigate the relationship between social studies pre-service teachers' (SSPTs) learning style, test anxiety and academic achievement. A total of 315 SSPTs participated in the study. Data were collected using Turkish versions of Grasha-Reichmann learning style scale (GRLSS) and test anxiety scale (TAS) by Spielberger. According to the findings, SSPTs' academic achievements had negative and low-level relationship with the TAS' worry sub-dimension while they had no significant relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
4
5
0
1
Order By: Relevance
“…In a class of 25 up to 30 students as the case in many classes in Jordanian schools, to listen and even to be less active participant in the learning process in the class, and later to double your efforts at home to accomplish your homework, might be the best approach to avoid being labeled as disabled ISSN 1948-5476 2020 learner. This result was consistent with the findings of (Becirovic, 2020;Cimermanová , 2018;Emejidio & Gepila, 2020;Lehman, 2019;Yazıcı, 2017), and this findings was support with better GPA achieved by students who prefer kinesthetic and auditory learning styles. In general, the more the learners are involved in the learning process, and more sensory inputs were utilized, the more they gain knowledge through learning situations (Yazıcı, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a class of 25 up to 30 students as the case in many classes in Jordanian schools, to listen and even to be less active participant in the learning process in the class, and later to double your efforts at home to accomplish your homework, might be the best approach to avoid being labeled as disabled ISSN 1948-5476 2020 learner. This result was consistent with the findings of (Becirovic, 2020;Cimermanová , 2018;Emejidio & Gepila, 2020;Lehman, 2019;Yazıcı, 2017), and this findings was support with better GPA achieved by students who prefer kinesthetic and auditory learning styles. In general, the more the learners are involved in the learning process, and more sensory inputs were utilized, the more they gain knowledge through learning situations (Yazıcı, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with the findings of (Becirovic, 2020;Cimermanová , 2018;Emejidio & Gepila, 2020;Lehman, 2019;Yazıcı, 2017), and this findings was support with better GPA achieved by students who prefer kinesthetic and auditory learning styles. In general, the more the learners are involved in the learning process, and more sensory inputs were utilized, the more they gain knowledge through learning situations (Yazıcı, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study found that there was a significant negative relationship only between the cognitive dimension of test anxiety and academic achievement. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
“…Test anxiety is defined as an emotional reaction or state of stress that occurs before examinations and continues throughout the examination period. [ 1 2 ]…”
Section: Introductionmentioning
confidence: 99%